The Weight of The Flock: Narratives of Young Men who were Childhood Herders in Lesotho - Malefane Justice Matele; Sophia Thabane (International Journal of Children, 2026)
Herding in Lesotho is associated with social isolation for extended periods, risk of assault by animal thieves, and risk of being attacked for suspected animal theft. Regardless, herding in Lesotho is mostly assigned to boys. The objective of this study was therefore to examine herding experiences of childhood herders in Thaba Tseka Lesotho. The study employed snowball sampling to recruit 14 childhood herders who were young adults (18-35 years old) at the time of the study. Data reported in this article were collected through in-depth face-to-face narrative interviews exploring experiences of childhood herding and analysed qualitatively. The findings revealed that, above everything, childhood herding was rife in Thaba Tseka. For instance, the age range of first herding experience for most participants was 6 to 9 years old while the youngest reported age at which participants were deployed to cattle posts was 8 years old. Further, herding was found to be strongly associated with school drop out with 5 participants not completing primary school and another 5 completing primary school only to pursue herding. Additionally, childhood herders worked with weather-inadequate attire, at unconducive cattle post dwellings, experienced food insufficiency, experienced sexual abuse, and had close encounters with death and dying. An asset-based intervention against childhood herding is therefore recommended for Lesotho and all countries experiencing labour-injustice against children. Thus, it is recommended that community policing forums should be trained on laws which protect children against all forms of child labour and charged with the responsibility to police and act against childhood herding.
Keywords: Childhood herders; Lesotho; community policing; herding; herding adversities